2019
DOI: 10.1111/ssqu.12620
|View full text |Cite
|
Sign up to set email alerts
|

Tiger Moms or Cat Dads: Parental Role in Bilingualism Among Asian and Latino Americans

Abstract: Objective. This study examines the differing roles of parents in producing bilingualism among second-generation Asian and Latino Americans, the fastest growing immigrant groups in the United States. Methods. We employ the probit model to estimate the likelihood of language maintenance for both ethnic groups using the Integrated Public Use Microdata Series (IPUMS) USA of 2005-2014. Results. The estimation results show that mothers play a more significant role than fathers, especially for Latino Americans, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the United States, confidence can be described as aggressive, charismatic, and promoting one’s agenda, whereas Asian Americans who are raised in a traditional (i.e., nonassimilated) Asian household may hold different cultural values and view such behavior as rude or brash (Hyun, 2012). Instead, most Asians are raised to show deference to elders, concede to authority, maintain native language proficiency, and refrain from asking questions or complain (Chen & Kang, 2019; Chin, 2016; Hyun, 2005; Zhou & Lee, 2017). However, to move up the executive ladder, educational achievement and intelligence are but only a small component to success (Ong & Hee, 1993; Takei et al, 2014).…”
Section: Model Minority Mythmentioning
confidence: 99%
“…In the United States, confidence can be described as aggressive, charismatic, and promoting one’s agenda, whereas Asian Americans who are raised in a traditional (i.e., nonassimilated) Asian household may hold different cultural values and view such behavior as rude or brash (Hyun, 2012). Instead, most Asians are raised to show deference to elders, concede to authority, maintain native language proficiency, and refrain from asking questions or complain (Chen & Kang, 2019; Chin, 2016; Hyun, 2005; Zhou & Lee, 2017). However, to move up the executive ladder, educational achievement and intelligence are but only a small component to success (Ong & Hee, 1993; Takei et al, 2014).…”
Section: Model Minority Mythmentioning
confidence: 99%
“…In Chinese culture, it is the norm for men to be the breadwinners and women to be the caregivers at home, so mothers are more involved in their children's education (53). In addition, in contemporary Chinese culture, the term "Tiger Mom, Cat Dad" has emerged, suggesting that mothers play a more strict and demanding role in family education (54), which makes the strong relationship between maternal parenting style and child OCD symptoms more plausible. As a result, the relationship between a mother's negative parenting style and a child's perfectionism and obsessive-compulsive symptoms is more closely related.…”
Section: Discussionmentioning
confidence: 99%
“…A gendered view of immigrant parenting has been the subject of research interests in IP research (e.g. Chen & Kang, 2019;Jorden et al, 2018;Poez, 2019). Immigrant mothers and fathers' fertility behaviors and their different parenting practices were highlighted.…”
Section: Gender Differencesmentioning
confidence: 99%
“…The substantial acknowledgement of parental support as promotor of children's family language development fostered a continuous research engagement on this topic. Past influential studies have focused on the role of parents in developing bilingual children (Chen & Kang, 2019), children's agentic actions in the use of languages (Said & Zhu, 2019), siblings as language socialization agents (Mina & Asta, 2018), and home language maintenance of immigrant children (Kaveh, 2018). Notwithstanding the importance of these studies, they had limitations and indicated areas for future research.…”
Section: Family Language Policiesmentioning
confidence: 99%